Factor Influencing of GCG and Service Quality to Increase Customer Loyalty in Islamic Bank - Zarkasyi, Muhammad Ridlo; Nurfattah, Arizqiya; Kamaluddin, Imam; Cahyani, Meitria (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This research aims to find out the effect of service quality and the implementation of GCG on customer trust, knowing the effect of trust on customer loyalty, and knowing the effect of service quality and the implementation of GCG on customer loyalty. The data that was successfully collected was then analyzed using SEM with AMOS 24 software. The findings in this study state that: a) The implementation of GCG affects customer trust, as well as the quality of service, and has a positive influence on customer trust. b) There is a positive and significant influence of customer trust on customer loyalty. c) the quality of service and the implementation of GCG do not affect customer loyalty. The existence of the customer trust factor as a mediator is getting stronger with no positive influence on service quality and GCG distribution on customer loyalty.